1991
DOI: 10.1097/00006842-199101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Regular hypnotic drug treatment in a sample of 32,679 Swedes: associations with somatic and mental health, inpatient psychiatric diagnoses and suicide, derived with automated record-linkage.

Abstract: We studied Swedish survey responders who reported regular treatment with hypnotic drugs, to find associations to perceived health problems, inpatient psychiatric diagnoses, and subsequent suicide. Among 32,679 sampled Swedes, 26,952 (83%) participated, 500 of which (2%) reported regular hypnotic drug treatment. The rate of treatment was higher in women, and increased by age in both sexes. The major findings were high odds of concurrent psychoactive drug treatments, nervous symptoms and insomnia, as well as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
3
16
1
Order By: Relevance
“…Among the users of sleep‐medication, individuals were more likely to take sleeping pills, with increasing the symptoms of insomnia. These results are consistent with previously reported findings in terms of the associations of sleep‐medication use with age and sex, 10–12,34–38 and insomniac symptoms 10,11,34,36–38 …”
Section: Discussionsupporting
confidence: 93%
“…Among the users of sleep‐medication, individuals were more likely to take sleeping pills, with increasing the symptoms of insomnia. These results are consistent with previously reported findings in terms of the associations of sleep‐medication use with age and sex, 10–12,34–38 and insomniac symptoms 10,11,34,36–38 …”
Section: Discussionsupporting
confidence: 93%
“…The first of these studies examined 26,952 adult Swedes between 1975 and 1981, 500 of whom (2%) were frequent hypnotic users (345 women, and 155 men), and tracked suicides until 1985 in the national Cause of Death Registry. (19) Subsequent suicides were found in 1.1% of hypnotic-treated women versus 0.1% of the women not taking hypnotics (OR=2.6, p<0.05). No men died by suicide.…”
Section: Resultsmentioning
confidence: 95%
“…Both the first and second Cancer Prevention Study (CPS I and II) have reported associations between early death and sleeping pill utilization [7, 30]. It has also been demonstrated that regular users of hypnotics often have disabling psychiatric and somatic conditions [48, 49], and are frequently treated with other psychoactive drugs [48, 50]. In one survey more than one‐third of female hypnotic users were receiving health care not for sleep problems but for depression, anxiety and other reasons [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the sales of tranquillizers and hypnotics/sedatives are a marker for poor socio‐economic conditions and correlate with both mortality and suicide [52]. Furthermore, males using hypnotics habitually were found to have higher rates of psychiatric admissions as a result of substance abuse whilst females had an increased risk of suicide [48].…”
Section: Discussionmentioning
confidence: 99%